Identification of a putative triacylglycerol lipase from papaya latex by functional proteomics - Ranajit Kumar Shaha (2010)
Latex from Caricaceae has been known since 1925 to contain strong lipase activity. However, attempts to purify and identify the enzyme were not successful, mainly because of the lack of solubility of the enzyme. Here, we describe the characterization of lipase activity of the latex of Vasconcellea heilbornii and the identification of a putative homologous lipase from Carica papaya. Triacylglycerol lipase activity was enriched 74-fold from crude latex of Vasconcellea heilbornii to a specific activity (SA) of 57 lmolÆmin)1Æmg)1 on long-chain triacylglycerol (olive oil). The extract was also active on trioctanoin (SA = 655 lmolÆmin)1Æmg)1), tributyrin (SA = 1107 lmolÆmin)1Æmg)1) and phosphatidylcholine (SA = 923 lmolÆmin)1Æmg)1). The optimum pH ranged from 8.0 to 9.0. The protein content of the insoluble fraction of latex was analyzed by electrophoresis followed by mass spectrometry, and 28 different proteins were identified. The protein fraction was incubated with the lipase inhibitor [14C]tetrahydrolipstatin, and a 45 kDa protein radiolabeled by the inhibitor was identified as being a putative lipase. A C. papaya cDNA encoding a 55 kDa protein was further cloned, and its deduced sequence had 83.7% similarity with peptides from the 45 kDa protein, with a coverage of 25.6%. The protein encoded by this cDNA had 35% sequence identity and 51% similarity to castor bean acid lipase, suggesting that it is the lipase responsible for the important lipolytic activities detected in papaya latex.